Pengaruh Nilai Ekspor dan Impor Migas-Nonmigas dan Nilai Tukar terhadap Inflasi di Indonesia Periode 1996-2021 - Melia Yunita Sari; Maulidiyah Indira Hasmarini (Ekonomis: Journal of Economics and Business, 2023)
International trade is a way to strengthen relations between a country and other countries, especially in the economic field. Indonesia is a country that has abundant natural wealth among other countries, such as oil and gas and non-oil and gas. Indonesia is an exporting and importing country of oil and gas and non-oil and gas. Inflation affects the value of exports and imports of oil and gas and non-oil and gas in Indonesia. This study aims to determine the direction and magnitude of exports and imports of oil and gas and non-oil and gas and the trade balance on inflation in the Indonesian region in 1996-2021. The method used is a quantitative method with multiple linear regression analysis or Ordinary Least Square (OLS) with secondary data collection through BPS and Bank Indonesia (BI). The conclusion of this study shows that Oil and Gas Exports-Non-Oil and Gas have no effect on Inflation, Imports of Oil and Gas-Non-Oil and Gases have an effect on Inflation and Exchange Rates have no effect on Inflation